The effect of Organizational Citizenship Behavior on Performance mediated by Job Satisfaction - Sri Wiyati Mahrani; Alwi, Saemu (International Journal of Management and Education in Human Development, 2022)
This study aims to examine and analyze the effect of OCB on performance, the effect of OCB on job satisfaction, the effect of job satisfaction on performance, and the effect of OCB on performance mediated by job satisfaction. The research subjects were the police at the Directorate of Intelkom Polda. Respondents in this study were all police at the Directorate of Intelkom Polda, 123 police. Data analysis techniques were carried out using PLS (partial least squares) where the process was assisted by smartPLS 3.0 software. The results of this study indicate that OCB has a significant effect on performance. OCB has a significant effect on job satisfaction. job satisfaction has a significant effect on performance. OCB has a significant effect on performance through job satisfaction